2021
DOI: 10.1186/s40729-021-00313-2
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of causal factors influencing accuracy of guided implant surgery for partial edentulism: a retrospective clinical study

Abstract: Background In dental implant treatment, the placement position of the implant body is important. The hypothesis is that there are factors that have a greater impact than the factors that have been studied so far. Material and Methods The deviation between planned and actually placed implants was measured three-dimensionally by modified treatment evaluation method in 110 patients who underwent implant placement with guided surgery for partial edentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…However, surgical guides supported by only two teeth demonstrated significantly higher deviation values than implants placed using surgical guides supported by four teeth or more. Moreover, Matsumura et al [10] showed that an insufficient number of teeth supporting the guide, or an excess of teeth supporting the guide can influence errors of implant positioning during guided surgery. Balance fit and stability were therefore not sufficient to allow an accurate implant placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, surgical guides supported by only two teeth demonstrated significantly higher deviation values than implants placed using surgical guides supported by four teeth or more. Moreover, Matsumura et al [10] showed that an insufficient number of teeth supporting the guide, or an excess of teeth supporting the guide can influence errors of implant positioning during guided surgery. Balance fit and stability were therefore not sufficient to allow an accurate implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…The deviation between the planned and effective implant position can be caused by multiple factors. Based on the literature, the error factors can be classified in three categories (i) clinical situation derived factor [8,9], (ii) implant system derived factors [10] and (iii) surgical guide design [11,12] and manufacturing derived factor [13,14]. For example, Putra et al [15] showed in a literature review that guides produced by a conventional method induce a higher angular deviation than a 3D-printed guide.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the prospective study design, a total of twenty-one retrospective non-RCTs [ 7 , 19 , 25 , 31 37 , 41 , 45 , 47 , 48 , 51 , 60 , 62 , 63 , 67 , 70 , 78 ] were assessed using Robin-I. According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the clinical outcomes of the fully guided system mainly depended on the operation and experience of surgeons, leading to hand tremors and inaccurate perception easily. 33,34 The intrinsic errors, such as the misfit of the guide or the metal sleeve and drills, affected the accuracy. Additionally, the positioning error of the 3D digital implant guide and interference of the opposing dentition hindering the correct positioning of the drills and implant might cause an operating error.…”
Section: Discussionmentioning
confidence: 99%
“…There were differences between autonomous robotic implant surgery and fully guided sCAIS in resulting accuracy. On one hand, the clinical outcomes of the fully guided system mainly depended on the operation and experience of surgeons, leading to hand tremors and inaccurate perception easily 33,34 . The intrinsic errors, such as the misfit of the guide or the metal sleeve and drills, affected the accuracy.…”
Section: Discussionmentioning
confidence: 99%